The Wager : a tale of shipwreck, mutiny, and murder [large type] - Grann, David (Random House Large Print, 2023)
"From the #1 New York Times bestselling author of Killers of the Flower Moon, a page-turning story of shipwreck, survival, and savagery, culminating in a court martial that reveals a shocking truth. The powerful narrative reveals the deeper meaning of the events on The Wager, showing that it was not only the captain and crew who ended up on trial, but the very idea of empire"--